Sustainable Food Systems and Regional Development: Analyzing Food Security in Medan City’s Underprivileged Areas, Indonesia - Muliadi, Muhammad; Lubis, Satia Negara; Harahap, Hamidah; Slamet, Bejo; Lubis, Arga Abdi Rafiud Darajat (Journal of Ecohumanism, 2024)
This study investigates the critical role of sustainable food systems in enhancing food security and regional development in the underprivileged areas of Medan City, Indonesia. Using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach, data were collected from 400 respondents across the city’s most impoverished districts. The findings indicate that sustainable practices in food availability, consumption patterns, and distribution systems are essential determinants of food security and regional development. By promoting local food production, encouraging balanced diets, and developing efficient distribution networks, policymakers can address food insecurity and support sustainable regional growth. The study underscores the necessity of integrating sustainability principles into food security strategies and regional development plans. This alignment with the Sustainable Development Goals (SDGs) aims to end hunger, achieve food security, and promote sustainable agriculture by 2030. Policy recommendations include investing in sustainable agricultural practices, improving infrastructure for food distribution, and implementing community-based nutrition education programs. These strategies are crucial for building resilient and equitable communities in Medan City and beyond.